Typing of Pseudomonas aeruginosa strains in Turkish cystic fibrosis patients - (:unkn) unknown (LUIGI PONZIO E FIGLIO, 2003)
The majority of cystic fibrosis (CF) patients suffer from chronic respiratory infection with the opportunistic bacterial pathogen Pseudomonas aeruginosa. The virulence of P. aeruginosa is associated with the presence of various extracellular factors, like alginate, elastase, alkaline protease which contribute tissue destruction and assist bacterial invasion. Virulence factor production of P. aeruginosa strains isolated from 46 CF patients followed in two cities in Turkey was detected. Strains were compared genotypically by arbitrarily primed PCR. Antimicrobial susceptibilities to 12 antibiotics were determined by broth microdilution method. Evaluation of virulence factor results revealed that 95.8% of the strains were alginate, 71.7% elastase and 52.1% alkaline protease producers. AP-PCR analysis revealed 35 genotypes indicated almost a complete discrepancy among the strains. The most efffective drugs were penems and quinolones. Among amino-glycosides amikacin was the most efffective one and a high level resistance to beta lactams was observed. Alginate is the most important virulence factor in the chronic colonisation of CF patients with P.aeruginosa. No evidence for cross infection between patients and for relationship between phenotypes and genotypes of the strains was found.
Keywords: cystic fibrosis; Pseudomonas aeruginosa; virulence factors; AP-PCR; antimicrobial susceptibility; CROSS-INFECTION